Margherita Marchione as Antihero for Italian Jews: A Complex Message of Hope - Vitale, L. (A Century of Italian War Narratives: Voices from the Sidelines, 2023)
Lisa Vitale discusses the intellectual contribution of historian and apologist Margherita Marchione in redefining the role of Pius XII during the atrocities of the Nazi Holocaust by means of personal narratives of the Sisters of St Lucy Filippini (of which Marchione was a member) and the Jewish refugees they sheltered, including the prominent Roman Di Veroli family. The chapter paints a multi-faceted, and sometimes contradictory, picture of Catholic charity during those turbulent and confusing times. Despite Marchione’s defense of Vatican (in-)action during the mass extermination of the Jews, she brings a message of hope to today’s Jewish Italian citizens. © 2023 by Koninklijke Brill NV, Leiden, The Netherlands.
Keywords: dept.wll